Análise da incidência e fatores de risco dos incidentes entre pacientes críticos: estudo de coorte concorrente - Daniela Mascarenhas de Paula Campos (2022)
Incidents are events or circumstances that could result or result in damage to the patient. When the damage occurs, the incident is considered an adverse event. In view of the impact of the incidents, patient safety has become a concern for managers and professionals, and it is essential to identify incidents and risk factors for their occurrence in different health services. Thus, this research was carried out with the objective of analyzing the epidemiological aspects related to the occurrence of incidents and non-conformities related to the prevention of incidents in the ICU. This is a concurrent, closed cohort study conducted with 173 patients hospitalized from September to November 2019. Patients were followed by admission to the outcome (discharge, death or end of the study). Data on sociodemographic and clinical catacterization of patients, occurrence of incidents, use of care devices and incident prevention practices were obtained. Descriptive and inferential statistics were performed. The incidents were classified as to the type and degree of damage, according to the International Patient Safety System. To estimate the incidence, the incidence density of the incidents was used. To analyze the association of covariates with the incident, binary logistic regression analysis was used, presenting the respective Odds Ratio and its 95% confidence interval. It was adopted as significant p<0.05. Among the patients, there was a predominance of the elderly (71.1%) and males (56.1%). During the evaluation, 144 incidents were found, and 35.0% of the admitted patients evolved with at least one incident. Incidence density was 134.5 incidents per 1,000 patients per day. Clinical process/pro-drop incidents were predominant (71.5%), with pressure injury being the most reported (32.0%). Regarding the damage, 64.6% were classified as mild, 20.1% moderate and 15.3% were incidents that did not present damage. In the final model of logistic regression, the length of stay in the sector and the time of use of central venous catheter were associated with a higher chance of incidents. From the evaluation of incident prevention practices adopted by nursing professionals, it was found an average support of pneumonia prevention actions. The incipience of studies in this area of knowledge, as well as the non-participation of professionals to prevention practices demonstrate the need to raise awareness about the importance of the theme and reorientation of professional practice.